2003
DOI: 10.1108/00483480310498666
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards benefits among entrepreneurial employees

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another vein for research would focus on examining how similar or different the results found here might be across other cultures and regions of the world (Carraher, 2003; Carraher et al , 2003a, b). It might also be useful, for example, to examine whether individuals from different countries perceive performance and reward problems in the same manner (Carraher and Buckley, 1996) and whether cultural differences influence the effectiveness of socialization processes, and subsequent performance, of new employees (Buckley et al , 1998, 2002) and internal hires (Bradley, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another vein for research would focus on examining how similar or different the results found here might be across other cultures and regions of the world (Carraher, 2003; Carraher et al , 2003a, b). It might also be useful, for example, to examine whether individuals from different countries perceive performance and reward problems in the same manner (Carraher and Buckley, 1996) and whether cultural differences influence the effectiveness of socialization processes, and subsequent performance, of new employees (Buckley et al , 1998, 2002) and internal hires (Bradley, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…(3) Rewards and reinforcement comprise the extent to which the organization implements schemes to offer its workers rewards in recognition of entrepreneurial undertakings and success. There is evidence to show that the characteristics of varying reward systems could influence individuals' conceptualization of benefits (Carraher et al, 2003), encourage them to take risks and innovate, and also have a powerful influence on their tendencies to behave in entrepreneurial ways. Specifically, if an individual is rewarded for displaying entrepreneurial behavior, he or she is more likely to engage in innovative, proactive, and moderate risk-taking behavior (Monsen et al, 2010).…”
Section: Organizational Support For the Intrapreneurial Behavior Of Employeesmentioning
confidence: 99%
“…More recently, the compensation literature has begun to explore the incentive effects of benefits. The management literature suggests that dissatisfaction with benefits may result in general job dissatisfaction, higher levels of absenteeism, and lower levels of performance (Carrahar, Hart, & Carrahar, 2003). Even and Macpherson (2001) posit that benefits can affect productivity by altering employees' incentives to invest in firm-specific knowledge.…”
Section: Compensation Objectives and Benefitsmentioning
confidence: 99%